Catalogue of Sabellidae (Annelida: Polychaeta) from the Grand Caribbean Region - Tovar-Hernández, María Ana; Salazar-Silva, Patricia (Zootaxa, 2008)
The most recent checklist of polychaete worms of the Grand Caribbean region dates from 1996. Since then systematic contributions for the family Sabellidae have been published resulting in changes in the taxonomic status of various genera and species. This catalogue provides new names, synonymies, new records and a list of corrected references. Twenty two genera and 51 species are listed. Fabriciinae is represented by 10 species and six genera and Sabellinae with 41 species and 16 genera. Sixteen species that were originally described from the Grand Caribbean region are currently recognised as not valid, and 11 records as questionable until any revision sustains their distribution. Information for type locality and location of type materials are included.